The Politics of Calendars: State Appropriations of the Contested Iranian Past - Kashfi, Ehsan (Religions, 2021)
This paper seeks to investigate how commemorative practices, rituals, and holidays are invented, deployed, and recast for political and ideological purposes, to reinforce and sustain a particular narrative of national identity. It argues that the choice of particular moments of a country’s past to be commemorated in calendars as national holidays and the way in which the collective past is preserved and remembered both reflect and articulate a country’s vision of its present essence, of who its people are. Recognizing the link between the collective memory and national identity, the Iranian states before and after the 1979 revolution made a special effort to articulate their narrative of the past by commemorating a particular set of holidays and rituals. Viewing the calendar as a political artifact, this paper compares changes in the Iranian national calendars in the Pahlavi era (1925-1979) and the Islamic Republic (1979-2018). It examines the inclusion of new religious holidays and the removal of national days associated with the monarchy as well as the assignment of new meanings and celebratory practices to the old ones as the signifiers of a political maneuver to articulate a new shared public memory and narrative of identity since the 1979 revolution. It then examines two nationwide celebrations before and after the 1979 revolution, representing two state-sponsored, competing narratives of Iranian identity: firstly, the 2500-year celebration of the Persian Empire in 1953, and, secondly, the Ashura commemoration, a religious gathering dedicated to the remembrance of Shia Imams. These commemorations provided the state a unique political opportunity to present its own appraisal of the past and, in turn, national identity.